Development of Physics Learning Media Using Articulate Soryline 3 for Students of Phase F of SMA N 1 Pasaman - Andini, Lia (Universitas Negeri Padang, 2025)
The development of technology in the digital era has a significant impact on the world of education, requiring educators to integrate technology into learning in order to improve the quality of education. However, in physics learning, obstacles are still found such as students concluding that physics lessons are difficult to understand because of the many formulas used so that they are difficult to memorize. In addition, teaching materials that are still in the form of printed books with dense material presentations make it difficult for students to understand the material. Students also tend to be passive and have never used learning media based on Articulate Storyline 3. Therefore, this study aims to develop physics learning media using Articulate Storyline 3 for phase F students at SMA Negeri 1 Pasaman with the Research and Development (R&D) method using the ADDIE model, which is limited to the Implementation stage. The subjects of the study were class XI F2 students, with research instruments in the form of validity and practicality questionnaires that were analyzed to assess the feasibility of the media. The results of the analysis showed that the physics learning media using Articulate Storyline 3 was very valid with a score of 82.40% based on the validation of two material expert lecturers and one media expert lecturer. This media is also considered very practical with a score of 89.74%, based on the assessment of 33 students and one physics educator. Thus, the physics learning media based on Articulate Storyline 3 is valid and practical to use in the physics learning process at SMA Negeri 1 Pasaman